Literature study: the community perception of rowing venue development in women's forest ecosystem, Youtefa Bay, Jayapura City, Papua - Vience Tebay; Ilham Ilham (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Women's forest in the local language called “Tonotwiyat” is a private space for women. Women's forests are not only limited to controlling disasters and neutralizing air pollution but are like mothers who provide life for local communities. This article is a literature study by conducting text and discourse analysis on socio-cultural events whose subjects are library materials. The results of this study indicate that the construction of the rowing venue has contributed to the damage to the women's forest ecosystem in Jayapura City. The tradition of protecting women's forests as a source of local food and as a place for character education for women is now starting to be eroded as a result of environmental pollution and land conversion. Rehabilitation is carried out as an effort by the government to preserve the damage to the mangrove ecosystem that has been affected by development. As a recommendation In addition to carrying out rehabilitation and revegetation, in the future it is necessary to expand by planting mangrove seedlings by colonizing new areas or extensification. Including the importance of regulations governing the protection and management of women's forests based on local wisdom adopted by the local community.Keywords:Women's forestMangrovesDevelopmentRowing venue